NUTRITIONAL STUDY of Anthrenus flavipes (LECONTE).(COLEOPTERA:DERMESTIDAE) ON DIFFERENT FOODMATERIALS - Yunis, May; Kaddou, Ibrahim; Abdulla, Laith (Iraqi Journal of Science, 2025)
Eight food materials were used. They affected differently the biology of thisbeetle. Females laid highest number of eggs when fed on raw wool (٤٥ eggs), thenon goats hair (٤٠.٤ eggs) lowest number of eggs (١٧.٢) when fed on natural silk, and(١٨ eggs) on sheep hide.Larval duration was shortest on raw wool (٧٨.٤ days), then goats hair (٨٤.٨ days)and camels hair (٩١.٨ days). It was largest on human hair (١٧٦ days) and natural silk(١٧٣ days). Larval mortality was lowest on goat’s hair (١%) then on raw wool (٤%)and highest on natural silk (١٦%) and human hair (١٢%). Other material lies between them. These materials affected variably pupal duration, adult emergence.Adult longevity when beetles were fed, as larvae. Raw wool and goats hair wasmore favorable for the beetle’s biology where as natural silk and human hair werethe least favorable. Other materials ranged between them. Protein content did notshow any correlation between these contents and the results of this investigation.